(untitled) (Journal of Libya for geographical studies, 2024)
The Study aims to know the fate of medical waste resulting from wet cupping center in Sirte city in terms of it is components, methods of Sorting and ways rid of them and laws and regulation of its work From the point view of officials and medical teams charging dealing with medical waste, and this study was approved on descriptive approach and indirect investigation method, and the target study Sample was formed from official and medical teams charged with medical waste. The random Sampling method was used which reached size of(5) centers in sirte city which approved in the health sector and the study reached number of results the most important of which : The volume of waste produced by the centers each month different from one center to another, and the type of waste components produced by the centers are similar and inclusive including gauze, warm materials, twill cotton, scalpels and needles. It was found the most of the centers does not Sort the medical waste produced by the Centers. The study concluded with a set of recommendations the most important which is the need to educate workers in medical centers and clinics in general and cupping centers in particular the serious dealing with medical waste and conducting awareness campaigns and medical brochures to these centers of which how to safety dispose of medical waste produced by these centers